Bibliometric Analysis of the Role of Employee Experience in Driving Digital Innovation - Loso Judijanto; Novian Aldo; Arnes Yuli Vandika (West Science Interdisciplinary Studies, 2024)
Digital innovation has become a critical driver of organizational transformation in the modern business landscape, and employee experience (EX) plays a pivotal role in facilitating this process. This study employs bibliometric analysis to explore the evolving research landscape on the relationship between EX and digital innovation. Using data from leading academic databases, the analysis identifies key themes, trends, and influential works in the field. Findings highlight the centrality of transformation, performance, and human-centric factors, such as leadership, knowledge sharing, and collaboration, in driving digital innovation. Emerging themes, including sustainability, green innovation, and digital literacy, underscore the shifting priorities in the literature. The study also reveals significant research gaps, including the need for more longitudinal studies, individual-level analyses, and insights from diverse cultural contexts. Practical implications suggest that organizations should adopt a holistic, employee-centric approach to digital strategies, integrating technological advancements with initiatives that enhance engagement, skill development, and sustainability. This study provides a foundation for future research and actionable insights for practitioners aiming to leverage EX for sustainable innovation.